PENERAPAN METODE BERMAIN PERAN UNTUK MENINGKATKAN KETERAMPILAN BERBICARA PADA SISWA KELAS III SD - Marsalinda; Khatimah, Khusnul; Ihsan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Speaking skills are one of the essential language competencies that elementary school students need to develop to communicate ideas, opinions, and experiences effectively. However, preliminary observations conducted in Grade III of SDN Inpres Dore indicated that many students experienced difficulties in speaking confidently, organizing ideas coherently, and using appropriate vocabulary during classroom activities. This study aimed to describe the implementation of the role-playing method and to improve students' speaking skills through classroom action research. The study employed the Kemmis and McTaggart classroom action research model, consisting of two cycles, with each cycle including planning, action, observation, and reflection stages. The research subjects were 13 third-grade students of SDN Inpres Dore. Data were collected through observation, performance tests, and documentation, and were analyzed using descriptive qualitative and descriptive quantitative techniques. Students' speaking skills were assessed based on pronunciation, intonation, fluency, vocabulary use, and self-confidence. The findings revealed that the implementation of the role-playing method successfully improved students' speaking skills. Learning mastery increased from 30.77% in Cycle I to 84.62% in Cycle II, exceeding the predetermined success criterion of 80% of students achieving the minimum mastery standard. In addition, students demonstrated greater participation, confidence, and communication skills during the learning process. Therefore, the role-playing method is considered an effective instructional strategy for improving speaking skills in elementary school students.